1982
DOI: 10.1161/01.res.51.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat stress on arterial baroreflex control of heart rate in the baboon.

Abstract: SUMMARY. The influence of environmental heat stress on the arterial baroreflex control of heart rate (HR) was studied in eight conscious, chronically instrumented baboons. Inflations of balloon occluders around the inferior vena cava (IVC) and thoracic descending aorta (DA) were used to produce acute, graded changes in mean arterial blood pressure (MABP) in 5 mm Hg intervals ranging from ±5 to ±25 mm Hg. After determination of the HR responses to changes in MABP in the normothermic baboon (blood temperature <3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
6
18
1
Order By: Relevance
“…The hemodynamic and thermoregulatory responses noted in the present study are consistent with, and extend, the findings of Gorman and Proppe (16). If we make the assumption that the heated animals are attempting to regulate MAP at a similar set point, it would follow that Moderate animals have a higher HR than Mild or Severe, as follows.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The hemodynamic and thermoregulatory responses noted in the present study are consistent with, and extend, the findings of Gorman and Proppe (16). If we make the assumption that the heated animals are attempting to regulate MAP at a similar set point, it would follow that Moderate animals have a higher HR than Mild or Severe, as follows.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the hemodynamic pattern during the first 24 h of recovery would fluctuate predictably with changes in T c . However, data from rats and primates indicate that ϳ60% of hyperthermia-related tachycardia is autonomic in origin, and only 40% is the direct result of temperature on the SA node (16). Given the strong autonomic influence on hemodynamic responses to heat stress, it is likely that changes in HR during periods of changing T c (e.g., during heat exposure and cooling) include a central role for autonomic mechanisms.…”
Section: The Present Study Provides Mechanistic Insight Into Hemodynamentioning
confidence: 99%
“…It is thought that the rapid shift of blood to the lower extremities induces a transient reduction of blood pressure in the early phase of orthostatic stress. This may be applicable especially during hyperthermia, where there is a reduction in the tachycardia response to sudden hypotensive stimulation (Gorman and Proppe 1982;Yamazaki et al 1997). Thus, while working in a hot environment, a sudden change of posture to a standing position should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies investigated the effects of heat stress on baroreflex function in rats (18,22) and baboons (10). With the use of different techniques, these investigators concluded that hyperthermic exposure either increased (22), decreased (18), or did not change (10) the gain expressing baroreflex control of heart rate.…”
mentioning
confidence: 99%